Three new species of Forcipomyia (Lepidohelea) (Diptera: Ceratopogonidae) from West Bengal, India - Pal, Gouri Sankar; Hazra, Niladri (Zootaxa, 2024)
Three new species of the subgenus Lepidohelea Kieffer, 1917 of the genus Forcipomyia were described from the northern region of West Bengal based on morphological data. Forcipomyia (L.) inflatistyla sp. n. was collected from the Dooars region (Jayanti, near the Core area of Buxa Tiger Reserve), while two new species F. (L.) ranula and F. (L.) sulcoa were procured from Kalimpong in the Eastern Himalaya. Discovery of the three new species raises the total number of species of the genus Forcipomyia to 86 in India. A key to the Indian species of Lepidohelea is also provided.